2004
DOI: 10.1073/pnas.0405375101
|View full text |Cite
|
Sign up to set email alerts
|

Alkalitolerance: A biological function for a multidrug transporter in pH homeostasis

Abstract: MdfA is an Escherichia coli multidrug-resistance transporter. Cells expressing MdfA from a multicopy plasmid exhibit multidrug resistance against a diverse group of toxic compounds. In this article, we show that, in addition to its role in multidrug resistance, MdfA confers extreme alkaline pH resistance and allows the growth of transformed cells under conditions that are close to those used normally by alkaliphiles (up to pH 10) by maintaining a physiological internal pH. MdfA-deleted E. coli cells are sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 41 publications
2
122
1
Order By: Relevance
“…This host is deficient in K ϩ /H ϩ as well as Na ϩ (Li ϩ )/H ϩ and Ca 2ϩ /H ϩ antiport (31)(32)(33). Tris⅐HCl was used instead of the Tris-Hepes used in earlier assays (11,12), and higher concentrations of K ϩ were tested in view of recent reports of several bacterial K ϩ /H ϩ antiporters with low affinity for cation (32,34). In assays of the B. subtilis YhaTU system, neither the transporter protein YhaU nor the ancillary protein YhaT exhibited K ϩ /H ϩ antiport activity at pH 8.5 when expressed individually.…”
Section: Cpa2mentioning
confidence: 99%
“…This host is deficient in K ϩ /H ϩ as well as Na ϩ (Li ϩ )/H ϩ and Ca 2ϩ /H ϩ antiport (31)(32)(33). Tris⅐HCl was used instead of the Tris-Hepes used in earlier assays (11,12), and higher concentrations of K ϩ were tested in view of recent reports of several bacterial K ϩ /H ϩ antiporters with low affinity for cation (32,34). In assays of the B. subtilis YhaTU system, neither the transporter protein YhaU nor the ancillary protein YhaT exhibited K ϩ /H ϩ antiport activity at pH 8.5 when expressed individually.…”
Section: Cpa2mentioning
confidence: 99%
“…Transport experiments have shown that MdfA is driven by the proton electrochemical potential (6,9,10), and in addition to its drug/proton exchange activity, it may also function as a (Na + ) (K + )/proton antiporter (11). Clearly, therefore, proton translocation by MdfA is crucial for all of its known biological activities.…”
mentioning
confidence: 99%
“…The C. glutamicum strains were grown at 31. 24) For the antimicrobial susceptibility assay, LB medium consisting of 10 g/l of tryptone, 5 g/l of yeast extract, and 10 g/l of NaCl (pH 7.2) was used.…”
Section: Methodsmentioning
confidence: 99%